Rock pools as a source of environmental DNA for the detection of the threatened Pilbara olive python (Liasis olivaceus barroni) - Mousavi-Derazmahalleh, M.; Ellis, R. J.; D’Rozario, B. L.; Berry, T. E.; Peverley, G.; Dawkins, K. L.; Campbell, M.; White, N. E.; Allentoft, M. E. (Frontiers in Environmental Science, 2023)
Environmental DNA (eDNA) research is transforming biomonitoring at a global scale, but applicability to reptiles has been restricted because of their presumed low shedding rate. Consequently, eDNA may have considerable limitations as a biomonitoring tool in Australia where 40% of the terrestrial vertebrates are reptiles. However, there is a need to evaluate if method improvements such as targeting certain substrates, improves the ability to detect reptile eDNA. The Pilbara olive python (Liasis olivaceus barroni) is an uncommon and elusive Australian top predator with a high conservation priority. Like many other snake species, Pilbara olive pythons are challenging to monitor with traditional survey methods, therefore exploring an eDNA-based approach is highly relevant. The pythons are known to occasionally reside in rock pools. Thus, development of a reliable eDNA-based approach to detect the pythons in water would provide a needed alternative method. Here we use a previously developed metabarcoding assay targeting reptiles, to sequence a total of 228 water samples collected from 40 rock pools from six broad locations across the Pilbara region of Western Australia, and we confirm the presence of Pilbara olive python eDNA in 37 samples from 12 of those pools at three of the six broad sampling locations. Other vertebrate taxa, including other reptiles, amphibians, mammals and birds were also detected. Our documented ability to detect Pilbara olive python eDNA from rock pool water samples represents an important step towards eDNA-based precision monitoring of this species.